2009
DOI: 10.1088/0957-4484/20/22/225107
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-assisted iron oxide magnetic nanoparticle immobilized keratinase

Abstract: Nanotechnology holds the prospect for avant-garde changes to improve the performance of materials in various sectors. The domain of enzyme biotechnology is no exception. Immobilization of industrially important enzymes onto nanomaterials, with improved performance, would pave the way to myriad application-based commercialization. Keratinase produced by Bacillus subtilis was immobilized onto poly(ethylene glycol)-supported Fe3O4 superparamagnetic nanoparticles. The optimization process showed that the highest e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 29 publications
(35 reference statements)
3
69
0
Order By: Relevance
“…The utility of curcumin, attributed with multiple therapeutic actions is however, limited by its color, poor water-solubility, and relatively low in vivo bioavailability. The recent quest for a 'supercurcumin' has led with numerous biomolecule immobilization studies being reported time and again [19]. Recently, iron oxide particles have been reported as potent free-radical scavengers [20].…”
Section: Introductionmentioning
confidence: 99%
“…The utility of curcumin, attributed with multiple therapeutic actions is however, limited by its color, poor water-solubility, and relatively low in vivo bioavailability. The recent quest for a 'supercurcumin' has led with numerous biomolecule immobilization studies being reported time and again [19]. Recently, iron oxide particles have been reported as potent free-radical scavengers [20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the elevation of native state activity of the enzyme may be responsible for the observed increase as reported for pectate lyase in the presence of hydroxyapatite nanoparticles [23]. Higher stability of keratinase exposed to iron oxide nanoparticles is also known [24]. As for the present investigation on nitrogenase, either one or all of these reasons may be responsible for the stimulatory response to ZnO nanoparticles application up to a certain concentration.…”
Section: Response To Bulk and Nano-zno In Legumesmentioning
confidence: 56%
“…Although a large number of nano-scaled carriers have been applied prior in the enzyme immobilization process (Kim et al, 2006), however, from an industrial perspective there are several disadvantages in this process owing to the difficulty experienced in recovering and handling the nanoparticles at the industrial level. Alternatively, the use of ironoxide magnetic nanoparticles (MNPs) might overcome such problems because utilizing magnets enables the simple recovery of the catalyst post binding with MNP (Tong et al, 2001;Konwarh et al, 2009). Besides the use of iron-oxide MNP as a support to immobilize the enzymes there are several other advantages including those of higher specific surface area resulting in the binding of a large quantity of enzyme , lower mass transfer resistance and less fouling (Huang et al, 2003) as well as its strong magnetism and low toxicity (Liang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It might be presumed that the covalent coupling with the cyanamide resulted in the inter and/or intra cross-linking of the alkarnase which provided better stability to the tertiary structure of the enzyme (Tong et al, 2001;Konwarh et al, 2009). These results suggest that the immobilized alkarnase possessed a higher affinity compared with the free alkarnase towards its substrates which might be attributed to either the increase in the surface area available to the enzyme moieties resulting in a better orientation and/or a change in the conformation of catalytic site of alkarnase producing the high catalytic efficiency (Huang et al, 2003;Konwarh et al, 2009).…”
mentioning
confidence: 99%